2021
DOI: 10.1109/ted.2021.3115993
|View full text |Cite
|
Sign up to set email alerts
|

Fully On-Chip MAC at 14 nm Enabled by Accurate Row-Wise Programming of PCM-Based Weights and Parallel Vector-Transport in Duration-Format

Abstract: Hardware acceleration of deep learning using analog non-volatile memory (NVM) requires large arrays with high device yield, high accuracy Multiply-ACcumulate (MAC) operations, and routing frameworks for implementing arbitrary deep neural network (DNN) topologies. In this article, we present a 14-nm test-chip for Analog AI inference-it contains multiple arrays of phase change memory (PCM)devices, each array capable of storing 512 × 512 unique DNN weights and executing massively parallel MAC operations at the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…This work focuses on NVM CiM arrays using phase-change memory (PCM) cells, specifically following a recent prototype in silicon by Khaddam-Aljameh et al (2021).…”
Section: Analog Cim Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…This work focuses on NVM CiM arrays using phase-change memory (PCM) cells, specifically following a recent prototype in silicon by Khaddam-Aljameh et al (2021).…”
Section: Analog Cim Backgroundmentioning
confidence: 99%
“…Non-volatile memory (NVM) approaches are particularly relevant to TinyML applications, where we need single-chip solutions with all memory on-chip, and with low leakage. A recent phase change memory (PCM) based CiM chip (Khaddam-Aljameh et al, 2021) demonstrated 10 TOPS/W at full utilization.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations